Indistorsi Ekstremisme Melalui Akseptabilitas dan Eksplorasi Perayaan Kultural Hinduisme di Jember, Indonesia Implikasinya dalam Dakwah dan Manajemen Sosial-Budaya - Khoirotul Islamiyah; Zaskia Putri (Fakultas Dakwah UIN KHAS Jember, 2025)
Religious extremism poses a significant threat to peace and social stability, particularly in Indonesia, where religious intolerance and violence are on the rise. According to the Setara Institute, there were 333 incidents of violations of religious freedom in Indonesia in 2022, marking a 19% increase from the previous year. Research is needed to understand how cultural acceptability can help mitigate extremism and enhance interfaith coexistence. This research seeks to explore how interfaith openness in Jember builds social capital and prevents extremism, examine the effectiveness of interfaith dialogue and community leadership in extremism prevention, investigate how interfaith participation in cultural celebrations strengthens community solidarity, and assess the importance of interfaith harmony in shaping social identity and preventing conflict. Using a qualitative approach, data were gathered through participatory observation and in-depth interviews with members of the Hindu community and surrounding residents. The findings include: 1) Theory of Religious and Social Tolerance: Interfaith openness in Jember fosters social capital through non-discriminatory participation, strengthening social cohesion and control, and preventing extremism through mutual trust. 2) Extremism and Social Response: Interfaith dialogue and community leadership effectively prevent extremism and maintain social stability. 3) Cultural Celebration and Inclusivity: Interfaith participation in celebrations enhances solidarity among residents. 4) Theory of Coexistence: Interfaith harmony is integral to the community’s social identity, supporting social stability and preventing future conflict.